2018
DOI: 10.1242/jcs.211391
|View full text |Cite
|
Sign up to set email alerts
|

Matrix elasticity regulates mesenchymal stem cell chemotaxis

Abstract: Efficient homing of human mesenchymal stem cells (hMSCs) is likely to be dictated by a combination of physical and chemical factors present in the microenvironment. However, crosstalk between the physical and chemical cues remains incompletely understood. Here, we address this question by probing the efficiency of epidermal growth factor (EGF)-induced hMSC chemotaxis on substrates of varying stiffness (3, 30 and 600 kPa) inside a polydimethylsiloxane (PDMS) microfluidic device. Chemotactic speed was found to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 76 publications
1
27
0
Order By: Relevance
“…In addition, the unexpected shared behavioral characteristic of these various cancer cells and a normal fibroblast line to undergo durotaxis most efficiently on the soft portion of durotactic gradients suggests that physiologically softer regions of the body, e.g., the brain and other soft-tissue regions, may be particularly susceptible to durotaxis-augmented invasion. Interestingly, mesenchymal stem cell chemotaxis toward EGF was recently reported to be more efficient on a soft substrate (50). Taken together, these independent findings on durotaxis and chemotaxis suggest that cells may respond most efficiently to both physical and chemical cues for directional migration in a softer, more compliant microenvironment.…”
Section: Discussionmentioning
confidence: 76%
“…In addition, the unexpected shared behavioral characteristic of these various cancer cells and a normal fibroblast line to undergo durotaxis most efficiently on the soft portion of durotactic gradients suggests that physiologically softer regions of the body, e.g., the brain and other soft-tissue regions, may be particularly susceptible to durotaxis-augmented invasion. Interestingly, mesenchymal stem cell chemotaxis toward EGF was recently reported to be more efficient on a soft substrate (50). Taken together, these independent findings on durotaxis and chemotaxis suggest that cells may respond most efficiently to both physical and chemical cues for directional migration in a softer, more compliant microenvironment.…”
Section: Discussionmentioning
confidence: 76%
“…Moreover, we reviewed the literature (ii) to elucidate if the biomaterials that have been used or are being used for clinical cartilage repair are known to utilize material stiffness for controlling cell functions. An important insight produced by this review is that both CHs and MSCs are highly susceptible to material stiffness, as CH morphology [ 167 , 169 ], proliferation [ 164 ], clustering [ 164 ], and phenotype [ 163 , 166 , 167 ], MSC migration [ 139 , 140 ], proliferation [ 121 ], morphology, lineage determination and differentiation [ 44 , 259 ] as well as certain immuno-modulative and angiogenic roles of MSCs [ 148 , 210 ] are stiffness-mediated. Thus, controlling material stiffness for guiding cell fate is undoubtedly an effective approach for experimentally controlling CHs and MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, traction forces from the cell are not transmitted to the ECM and, consequently, the cell does not move. Depending on the magnitude of the elastic modulus, hMSCs migrate faster on softer substrates such as 3 kPa and form smaller FAs, compared to a slower movement on substrates with a higher elastic modulus such as 30 and 600 kPa [ 139 ]. However, on gradients within the range of physiologically relevant elastic moduli for soft tissues (i.e., 1–12 kPa), hMSCs migrated to the stiffest region on each gradient and their migration speed correlated with the gradient strength [ 140 ].…”
Section: Materials Stiffness-regulated Cell Migrationmentioning
confidence: 99%
“…Amniotic fluid-derived stem cells (AFSCs) cultured on softer substrates (2 kPa) secreted more autocrine cytokines, which increased AFSC migration compared to cells cultured on plastics (~100,000 kPa) by transwell assay [76]. A study involving epidermal growth factor-induced chemotaxis of human MSCs, through polydimethylsiloxane microchannels with varying substrate stiffness, showed that under an identical chemokine gradient, human MSCs migrated fastest on 3 kPa soft substrates associated with the formation of smaller adhesions when compared to stiffer substrates (30 kPa and 600 kPa) [77].…”
Section: Mechanical Factors Regulating Bmsc Migrationmentioning
confidence: 99%